Evaluation of audio-visual aids as a medium of periodontal health education for patients with periodontitis - K. B., Menaka; Raza, Sidra; U. Nayak, Sangeeta; Krishna, Vinita (International Journal Of Community Medicine And Public Health, 2023)
Background: It is of paramount importance that patients be educated of their clinical conditions and the available treatment options. Audio-visual aids can be used as a beneficial modality to help the clinicians in the educational task by presenting the necessary information to the patient in a simpler manner. Methods: A randomized controlled trial was done to assess the retention of knowledge amongst periodontitis patients after receiving oral health education using audio-visual aids. The effect of audio-visual aids was compared to standard education in the form of verbal narration for periodontal patient education. A total of 60 consented periodontitis patients were recruited for the study and randomly allocated to audio-visual group or control group according to computer generated randomization. All patients received a pre-test questionnaire to assess their baseline knowledge regarding oral health and treatment modalities. A post-test questionnaire was taken immediately after receiving the two sets of education to assess the retention level of knowledge. The questionnaire contained 15 multiple-choice questions. Results: There was no significant difference in baseline knowledge between the two groups (p value=0.317). Patients receiving the audio-visual aids had significantly higher scores for the post-test (mean±SD=7.56±2.31) when compared with patients receiving standard education (mean±SD=5.73±2.94; p value=0.01*). Conclusions: Retention of knowledge is significantly higher in the audio-visual group when compared to the control group. Audio-visual aids can be an effective medium for patient education in day-to-day dental practice.